STUDY OF GENETIC DIVERSITY USING MICROSATELLITE MARKERS IN IRAQI SHEEP BREEDS - & et al., Hadi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Genotypes and allele frequency values ​​were studied to determine the genetic diversity of three microsatellite markers (BM1329, BM134 and CSSM66) in two local Iraqi sheep breeds (50 Awasi ewes (AW) and 50 Naimi ewes (NA)) and breed in one Agricultural Stations in middle of Al-Furut Iraq (Karbala Governorate). The Genetic analyses for the study were carried out at the Biotechnology Research Center /  Al-Nahrain University using PCR technology to obtain alleles for the studied microsatellites. The results of this study indicate that there is a multiplicity of genotypes and alleles resulting from these markers among the members of the single breed and between the studied breeds. It was revealed that the allele frequency values showed the presence of alleles dominant on the rest of alleles produce in this sample studied, the BM1329 microsatellite of the Awassi breed produced the dominant allele frequency in 195(0.25) and 320 (0.25), While in the Naimi breed were the values ​​of the dominant allele frequency of the195(0.22), 220(0.21) and 230(0.24), and the dominant allelic frequency of (BM134) marker in the Awassi breed was 118 and 135 and repeated (0.21 and 0.26, respectively). For CSSM66 microsatellite, the dominant allelic results and their allelic frequency values ​​were (195 (0.20), 205 (0.23) and 220 (0.25)) for Awasi breed, whereas it was 180 (0.24), 195 (0.28) and 220 (0.22) for Nuaimi breed. These results enable us to use these markers as a means of determining the diversity and genetic relationships between individuals of a single breed as well as between breeds.